2011
DOI: 10.1016/j.jcm.2011.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Chiropractic management of a 30-year-old patient with Parsonage-Turner syndrome

Abstract: Objectives: The purpose of this case report is to describe the chiropractic management of a patient presenting with right arm paralysis and a diagnosis of Parsonage-Turner syndrome. Clinical Features: After receiving nerve entrapment release surgery, a 30-year-old man presented with a right arm contracture, atrophy, and weakness with general paralysis of the forearm and index finger of 6 weeks' duration. Intervention and Outcome: The patient was provided chiropractic care that included highvelocity/low-amplitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Eight patients presented muscle alteration in the form of edema, associated with signs of hyperactivity, and the infraspinal and supraspinal muscles were the most affected 6 . A case report showed that PTS compromises functionality due to loss of mobility in the elbow region, forcing continuous maintenance of the flexion position 10 . A clinical trial showed that there is no consensus in the literature about which was the most affected peripheral nerve, which justifies the variety of symptoms and muscles affected by PTS 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight patients presented muscle alteration in the form of edema, associated with signs of hyperactivity, and the infraspinal and supraspinal muscles were the most affected 6 . A case report showed that PTS compromises functionality due to loss of mobility in the elbow region, forcing continuous maintenance of the flexion position 10 . A clinical trial showed that there is no consensus in the literature about which was the most affected peripheral nerve, which justifies the variety of symptoms and muscles affected by PTS 1 .…”
Section: Discussionmentioning
confidence: 99%
“…The conditions of patients with PTS are varied, so diagnosing the syndrome is a challenge 10 . In that sense, the knowledge of health professionals about the manifestations of PTS is essential for proper diagnosis and treatment.…”
mentioning
confidence: 99%